1998
DOI: 10.1111/j.1945-5100.1998.tb01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of gaseous elements and isotopes in a thermally evolving chondritic planetesimal

Abstract: Abstract-The behavior of H, C, N and their isotopes in a thermally evolving planetesimal was evaluated by numerical simulation. Transportation of heat and gas molecules, and the chemical equilibrium involving these elements, were simulated. Our modeled planetesimals initially contain homogeneous amounts of radioactive heat source (26A1); and H, C, and N in forms of organic materials, graphite, and in some models, water ice. Vaporized gas molecules were transported from the interior of the planetesimal to its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…For example, the vigor of C and N release from organics during thermal metamorphism depends on the redox conditions, particularly for C, which is incorporated into a gas under oxidizing conditions, but is stabilized in refractory compounds at more reducing conditions (23). This could account for much of the variation in C/N ratio seen in ordinary chondrites.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the vigor of C and N release from organics during thermal metamorphism depends on the redox conditions, particularly for C, which is incorporated into a gas under oxidizing conditions, but is stabilized in refractory compounds at more reducing conditions (23). This could account for much of the variation in C/N ratio seen in ordinary chondrites.…”
Section: Significancementioning
confidence: 99%
“…Volatile species, including some organics, would decompose in meteorite parent bodies at high temperatures and the liberated C and N could migrate to the surface as a gas and be lost to space or could be incorporated into metallic Fe,Ni (kamacite and taenite), owing to their siderophilic behavior (23). Thus, the abundances of both C and N are expected to diminish within bodies that were exposed to higher temperatures and more prolonged heating.…”
Section: Significancementioning
confidence: 99%
“…However, Schaefer and Fegley (2007) did not present results for the nominal pressure and temperature conditions proposed for Earth's putative steam atmosphere or consider several of the questions addressed in this paper. Hashizume and Sugiura (1998) did chemical equilibrium calculations of carbon speciation during metamorphism of ordinary chondritic material. They reported that CO was the major C-bearing gas, but as noted by Schaefer and Fegley (2007), after reading a preprint of their paper Professor Sugiura discovered that Hashizume and Sugiura (1998) used incorrect Gibbs energy data for CH 4 .…”
Section: Planet He Used H Chondritic and Various Mixtures Of H And Cmentioning
confidence: 99%
“…Antarctic CKs appear to have suffered less terrestrial contamination. Gibson and Yanai (1979) Despite the limited data available for CKs it is clear that total carbon contents tend to decrease with increasing metamorphic grade, a feature also seen in both the ordinary (Hashizume and Sugiura, 1998) and CO chondrites . As a defining characteristic of the CK group total carbon content is of limited value.…”
Section: Carbon Contentmentioning
confidence: 99%